2016
DOI: 10.3892/ol.2016.4643
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-type POZ (pox virus and zinc finger protein) protein gene deletion in ovarian cancer: Fluorescence in situ hybridization analysis of a tissue microarray

Abstract: The aim of the present study was to investigate the status of speckle-type POZ (pox virus and zinc finger protein) protein (SPOP) gene located on chromosome 17q21 in ovarian cancer (OC). The present study evaluated a tissue microarray, which contained 90 samples of ovarian cancer and 10 samples of normal ovarian tissue, using fluorescence hybridization (FISH). FISH is a method where a SPOP-specific DNA red fluorescence probe was used for the experimental group and a centromere-specific DNA green fluorescence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Studies on tumors have reported that SPOP may participate in the regulation of cell proliferation and apoptosis in a variety of tumors. Previously, we have found that the SPOP gene locus has a high-frequency deletion or loss of heterozygosity in ovarian cancer 22. However, the role of SPOP in ovarian cancer and its mechanism have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on tumors have reported that SPOP may participate in the regulation of cell proliferation and apoptosis in a variety of tumors. Previously, we have found that the SPOP gene locus has a high-frequency deletion or loss of heterozygosity in ovarian cancer 22. However, the role of SPOP in ovarian cancer and its mechanism have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The differential effect of SPOP in renal clear cell carcinoma and other cancers may be due to differences in the subcellular localization of SPOP in different cancers. In addition, we have previously identified high-frequency LOH in the SPOP locus in ovarian cancer tissues by fluorescence in situ hybridization (FISH) and suggested that SPOP may play a role in ovarian cancer 22. However, such a role and the related mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Only one group indicated that overexpression of the SPOP protein was essential for the apoptosis of HeLa cells, while this proapoptotic function was countered by ablation of SPOP [28]. Furthermore, one study used a tissue microarray to reveal a deletion mutant of SPOP in the majority of OC tissues that was not found in normal ovarian tissues, and this deletion mutant was correlated with high histological type and grade in OC [49]. Similarly, Jiang et al identified several novel mutations in OC cell lines and tissues through wholeexome sequencing, including mutations in SPOP [50].…”
Section: Cervical Cancer (Cc) and Ovarian Cancer (Oc)mentioning
confidence: 99%
“…Protein analysis by Hu et al found that more than 50% of ovarian cancer samples carried loss-of-function mutations of SPOP compared to 0% in adjacent tissues. Meanwhile, an inverse correlation exists between the tumor clinic pathological grade and the positivity of SPOP [201]. With regard to breast cancer, its proliferative and migratory potentials may be restricted due to SPOP-induced degradation on SRC-3 and PR (progesterone receptor) in vitro and in vivo, which usually amplifies the estrogen/progesterone-mediated expansion and dispersion of breast cancer cells [166,202,203].…”
Section: Gynecological Malignanciesmentioning
confidence: 99%
“…Tumor suppressor in gastric cancer [210] Urological system ) and xenografts in nude mouse) [181,196] 2 Tumor promoter in ccRCC (Xenografts in nude mouse) [223] 1 Tumor suppressor in prostate cancer [29] 2 Tumor promoter in ccRCC [223] Gynecological system Physiology Normalizing decidualization of endometrial stromal cells in mice [179] Normalizing decidualization of endometrial stromal cells [179] Tumorigenesis Tumor suppressor in breast cancer (Xenografts in nude mouse) [166] 1 Tumor suppressor in ovarian cancer cells [201] 2 Tumor suppressor in breast cancer cells [203] 3 Tumor suppressor in endometrial cancer cells [205] Musculoskeletal Compounds that directly target Cullin 3-based E3 ligases.…”
Section: Klhl21mentioning
confidence: 99%